(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
In this paper, a wideband circular patch antenna incorporated with a rectangular slot-loaded defective ground structure (DGS) is presented, meant for n77, n78, n79, and C band applications. The circular radiation patch of the proposed antenna is fed by a coplanar waveguide (CPW) mounted on a FR4 PCB board. At the bottom side of the board, a rectangular slot loaded on the DGS is added to establish good 50 Ω impedance matching and improve the antenna impedance bandwidth. This wideband antenna excites TM11 and higher-order TM21 modes at two distinct frequencies (3.3 GHz and 6.0 GHz). This circular patch antenna exhibits wideband behaviour with a fractional bandwidth > 90%, and an average efficiency of 76%.